Frequencies and functions of vocalizations and gestures in the second year of life - Megan M. Burkhardt-Reed; Edina R. Bene; D. Kimbrough Oller (PLoS ONE, 2025)
Speculations on the evolution of language have invoked comparisons across human and non-human primate communication. While there is widespread support for the claim that gesture plays a central, perhaps a predominant role in early language development and that gesture played the foundational role in language evolution, much empirical information does not accord with the gestural claims. The present study follows up on our prior work that challenged the gestural theory of language development with longitudinal data showing early speech-like vocalizations occurred more than 5 times as often as gestures in the first year of life. Now we bring longitudinal data on the second year (13, 16 and 20 mo), showing again that vocalizations predominated, and especially in conventional (learned) communication; > 9 times more spoken words were observed than gestures that could be viewed as functionally equivalent to words (i.e., signs). Our observations also showed that about ¾ of gestures across these second-year data were deictics (primarily pointing and reaching), acts that while significant in supporting the establishment of referential vocabulary in both spoken and signed languages, are not signs, but have single universal deictic functions in the here and now. In contrast, words and signs, the primary semantic components of spoken and signed languages, are functionally flexible, making possible reference to abstractions that are not bound to any particular illocutionary force nor to the here and now.